Epithelioid trophoblastic tumor of the uterus: A case report with radiologic–pathologic correlation. Issue 8 (26th May 2017) - Ohya, Ayumi; Higuchi, Kayoko; Shimojo, Hisashi; Fujinaga, Yasunari; Kadoya, Masumi; Shiohara, Shigeki
Abstract: Herein, we report a rare case of an epithelioid trophoblastic tumor of the uterus with radiologic–pathologic correlation in a 56‐year‐old postmenopausal woman. On T2‐weighted magnetic resonance (MR) imaging, the tumor appeared as a hypointense irregular mass compared with the surrounding myometrium of the uterine corpus and encircled the cavity of the lower uterine segment. On dynamic contrast‐enhanced MR images, the tumor appeared as a hypovascular mass and an inhomogeneously hyperintense mass in the delayed phase. In addition, non‐contrast computed tomography images showed some spotty areas of very high density within the tumor. These radiologic findings were well correlated with the histological features, such as abundant hyalinization and calcification within the tumor. Accurate interpretation of MR and computed tomography findings was helpful to differentiate epithelioid trophoblastic tumor from other gestational trophoblastic diseases and uterine carcinomas.